AIR POLLUTANTS INDUCED HAIR FALL - Priyanka V. Patil; Rahul K. Kamble (The Bioscan, 2025)
Hair fall is a common concern among human beings. The bodily factors are proven to be responsible for it. However, in addition to it,external environmental factors are also responsible for the same. This paper sheds light on the various air pollutants viz. particulate matter including dust suspended, respirable, and fine particulate matter and gaseous pollutants viz. sulphur dioxide, oxides of nitrogen, polycyclic aromatic hydrocarbons, volatile organic compounds, carbon monoxide, carbon dioxide,ultra violate radiation and humidity responsi ble for human hair fall and the mechanism involved in it.